Targeting a Large Active Site: Structure‐Based Design of Nanomolar Inhibitors of Trypanosoma brucei Trypanothione Reductase. Issue 49 (13th August 2019) - De Gasparo, Raoul; Halgas, Ondrej; Harangozo, Dora; Kaiser, Marcel; Pai, Emil F.; Krauth‐Siegel, R. Luise; Diederich, François
Abstract: Trypanothione reductase (TR) plays a key role in the unique redox metabolism of trypanosomatids, the causative agents of human African trypanosomiasis (HAT), Chagas' disease, and leishmaniases. Introduction of a new, lean propargylic vector to a known class of TR inhibitors resulted in the strongest reported competitive inhibitor of Trypanosoma ( T .) brucei TR, with an inhibition constant K i of 73 nm, which is fully selective against human glutathione reductase (hGR). The best ligands exhibited in vitro IC50 values (half‐maximal inhibitory concentration) against the HAT pathogen, T. brucei rhodesiense, in the mid‐nanomolar range, reaching down to 50 nm. X‐Ray co‐crystal structures confirmed the binding mode of the ligands and revealed the presence of a HEPES buffer molecule in the large active site. Extension of the propargylic vector, guided by structure‐based design, to replace the HEPES buffer molecule should give inhibitors with low nanomolar K i and IC50 values for in vivo studies. Abstract : Potency improvement by rational design: Trypanothione reductase (TR) is a drug target for trypanosomatidae‐caused diseases. By optimizing known TR ligands and using structure‐based design, a new series of potent TR inhibitors with target and cell‐based activities in the middle to upper nanomolar range was developed. X‐Ray co‐crystal structures confirmed the binding modes and revealed opportunities for a further increase in ligand potency towards in vivo studies.